Enhancement of critical current density in Mg-added ex-situ MgB2 through hydroxyapatite (HAp) doping - Tran, Duc H.; Do, Phuong T.; Cuong, Le Viet; Le, Tien; Chu, Minh Duy; Phuong, Nguyen Thu; Thanh, Dinh Thi Mai; Pham, An T.; Nam, Nguyen Hoang; Truong, Anh D.; Mohd Alimi, Nur Humaira Yasmin; Chen, Soo Kien; et al. (Elsevier, 2026)
Effect on superconducting properties of bulk polycrystalline ex-situ MgB2 samples with 0.5 mol Mg addition and various hydroxyapatite (HAp) doping levels (x = 0, 2, 4, 6, and 10 wt%), fabricated via the conventional solid-state sintering route, was investigated. Transmission electron microscopy (TEM) shown that the HAp powder contains well-dispersed nanoparticles with an average size of ∼110 nm, suitable for microstructural variation. X-ray diffraction (XRD) confirms MgB2 as the dominant phase, accompanied by minor MgO and CaB6 phases. The onset critical temperature (Tconset) shows only slight reductions, decreasing from 38.92 K (S0) to 38.27 K (S5), indicating negligible substitution into the MgB2 lattice. Field-emission scanning electron microscopy (FESEM) and energy dispersive X-ray spectroscopy (EDS) mapping provided important grain refinement, improved intergranular connectivity, and uniform dispersion of Ca-containing nano-inclusions within the MgB2 superconductor. The doped sample (S2) exhibits the highest specific field value Jc of 4.684x105A/cm2and superior performance in low and medium magnetic fields, indicating the balanced contribution of improved intergranular coupling and effective flux pinning. Flux pinning analysis further indicates that the dominant surface pinning mechanism was maintained across all compositions, with HAp-derived nano-inclusions providing additional pinning contributions. These results demonstrate that HAp was a promising pinning additive, with the optimal doping level of 2 wt% for enhancing the high-field performance of Mg-incorporated ex-situ MgB2 superconductors.